The Effect Of (Ableton) And (John Zahorek) Samples On The Achievement Of Fifth-Grade Students In The Biological Field Of Chemistry And The Development Of Their Adequate Cognitive Representation - Dr. Jehan Faris yousif, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to identify (the model effect of (Ableton) and (John Zahorek) in the achievement of fifth-grade students in the biological and development of their cognitive representation adequacy.) For the purpose of verifying this, three main hypotheses were imposed, so the researcher used the experimental method and chose Equal groups with pre and post-test, the study community consisted of students of the fifth grade of biological in the preparatory and secondary schools of the General Directorate of Karkh Education for the third academic year (2019-2020) for the purpose of applying the experiment, the study sample reached (94) students of the fifth grade of biology Three groups, two experimental and one control, as the number of the first experimental group was (30) students who studied according to the John Zahorek model, and the number of the second experimental group (30) students who studied according to the standardized method, and the number of students who studied according to the Appleton model was 34. The researcher rewarded the three research groups in a number of variables: intelligence, chronological age in months, The previous achievement, a measure of pre-cognitive representation. The researcher prepared the necessary tools for his current study, which included an achievement test consisting of (35) objective and essay items, and a cognitive representation scale consisting of (35) items with three alternatives within (5) skills or fields, and extracted the psychometric characteristics necessary for the study tools and the researcher applied the tests. The researcher herself carried out the experiment, which took one semester to implement, and after completing the experiment, the tests were applied to the study sample for the purpose of verifying the validity of her hypotheses and after processing the data through the SPSS program, the study revealed a number of results, including the existence of statistically significant differences between The experimental and control groups in the outcome test and the cognitive representation scale for the benefit of the experimental groups and based on the results of the current study, the researcher reached a set of conclusions, including the effectiveness of the Betton model and the John Zahorek model in light of the overall achievement test and the development of the study. (Ableton and John Zahorek) on the test of achievement and development Cognitive representation in the subject of chemistry, and the inclusion of curricula for teaching methods in colleges of education in Iraqi universities are typical (Ableton and John Zahorek). The researcher suggested conducting a number of future studies.